Muhammad's heirs the rise of Muslim scholarly communities, 622-950 - Brockopp, Jonathan E. (Cambridge studies in Islamic civilization, 2017)
Muslim scholars are a vital part of Islam, and are sometimes considered 'heirs to the prophets', continuing Muhammad's work of establishing Islam in the centuries after his death. By analysing coins, papyri and Arabic literary manuscripts from the ancient mosque-library of Kairouan, Tunisia, Brockopp offers a new interpretation of Muslim scholars' rise to positions of power and influence, serving as moral guides and the chief arbiters of Muslim tradition.